1955
DOI: 10.1083/jcb.1.6.501
|View full text |Cite
|
Sign up to set email alerts
|

The Demonstration of a Blood-Ocular Barrier in the Albino Rat by Means of the Intravitam Deposition of Silver

Abstract: Silver nitrate administered to rats in their drinking water from 6 months to a year or more, results in generalized argyria (1). I n the central nervous system, the intravitam deposition of the silver, as revealed by histological and electron microscopical examinations (Wislocki and Leduc, (2); Dempsey and Wislocki, (3)), approximates the pattern of the hematoencephalic barrier.I n the further course of examining silver-treated albino rats, we have noriced that silver accumulates mainly in two regions of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

1956
1956
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…However, a previous histopathologic study in albino rats did not show any accumulation of silver deposits in RPE cells,10 and furthermore, the fundus autofluorescence images from our patient did not show any signs of RPE damage. To our knowledge, there is only one previous report describing choroidal and retinal changes in patients with ocular argyrosis by means of fundus photographs and fluorescein angiography 9.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…However, a previous histopathologic study in albino rats did not show any accumulation of silver deposits in RPE cells,10 and furthermore, the fundus autofluorescence images from our patient did not show any signs of RPE damage. To our knowledge, there is only one previous report describing choroidal and retinal changes in patients with ocular argyrosis by means of fundus photographs and fluorescein angiography 9.…”
Section: Discussioncontrasting
confidence: 51%
“…Wislocki and Ladman conducted an experiment in albino rats involving giving them water containing silver nitrate for a period of 6 months to a year and trying to demonstrate the blood-ocular barrier. They reported histopathologic data showing that silver accumulated in two regions of the eye, ie, the ciliary processes and Bruch’s membrane 10. They also noted that the longer silver nitrate was administered, the greater the amount that accumulated.…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts to identify the organic material within the otoconial membrane histochemically have yielded various results. Some authors have shown the presence of glycoprotein based on periodic acid Schiff (PAS) staining (Wislocki and Ladman, 1955;Belanger, 1960;Igarashi and Alford, 1969;Ross, 1973). Belanger (1953Belanger ( , 1956Belanger ( , 1960 using iron adsorption and metachromatic staining with toluidine blue, indicated the presence of glycosaminoglycan which may (Belanger, 1960) or may not (Vilstrup and Jensen, 1954) be sulfated.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the mineral is calcium carbonate in the form of calcite. The precise composition of the organic phase is unknown, but it consists of protein and carbohydrate according to results from histochemical (Wislocki and Ladman, 1955;Belanger, 1960) and biochemical studies (Ross and Pote, 1984;Ross et al, 1985;Gil-Loyzaga et al, 1985).…”
mentioning
confidence: 99%
“…In adult animals, vital staining and phagocytosis can be observed only after the administration of very large doses or after injury to the eye, such as puncture of the anterior chamber (Schnaudigel, 1913;Hamburg, 1957). This is probably due to the development of the hemato-ocular bar¬ rier in the adult animal (Towbin, 1933;Wislocki and Ladman, 1955). Injection of colloidal material into the vitreous body results in phagocytosis, accompanied by an increase in the number of cells in the vitreous body as a result of cellular infil¬ tration (Potiechin, 1878;Gray, 1933;Ham¬ burg, 1957).…”
Section: Sections Of the Vitreous Body And Thementioning
confidence: 99%